Effects of Phosphorus Fertilization on Growth Characteristics, Fatty Acid Composition, and Seed Yields of Fengdan (Paeonia ostii T. Hong & J. X. Zhang) - Duan, Xiangguang; Liu, Wei; Wang, Xiaojing; Zhang, Lixia; Liu, Shuguang; Guo, Lili; Guo, Dalong; Hou, Xiaogai (HortScience, 2022)
Paeonia ostii T. Hong & J. X. Zhang is a perennial oil and medicinal plant with great importance as well as landscaping. P. ostii is being extensively planted in China, but the soil fertility limits the yield and quality. There is little information available on the effects of phosphorus fertilization on productivity, physiological characteristics, and seed yield and quality. This study investigated the influence of different phosphorus levels, 0 kg·hm −2 (CK), 90 c −2 (P1), 135 kg·hm −2 (P2), 180 kg·hm −2 (P3), 225 kg·hm −2 (P4), and 270 kg·hm −2 (P5), on the photosynthesis, morphology, physiological parameters, and yield of P. ostii . The results indicated that the net photosynthetic rate, stomatal conductance ( g S ), and transpiration rate of P. ostii increased significantly with the application of P4, which increased by 34.77%, 65.72%, and 21.00% compared with CK, respectively. Simultaneously, the contents of soluble sugar, soluble protein, and photosynthetic pigment in P4 were the highest compared with other treatments. In addition, thousand-grain weight (326.4 g) and seed yield per plant (37.33 g) of P4 were significantly higher than the control. However, the total amount of unsaturated fatty acids in P4 was lower compared with other treatments. The indexes of high correlation coefficients with Dim 1 and Dim 2 were g S and superoxide dismutase (SOD), respectively. The results showed that phosphorus levels improved plant photosynthetic capacity and increased antioxidant capacity as well as seed yield. Furthermore, phosphate fertilizer had significant effects on the oil composition. Moreover, the effect of phosphorus application rate on the growth index of P. ostii was greater than that of the physiological index.